2013
DOI: 10.1016/j.pbb.2013.05.011
|View full text |Cite
|
Sign up to set email alerts
|

Time of day influences the voluntary intake and behavioral response to methamphetamine and food reward

Abstract: The circadian timing system influences a vast array of behavioral responses. Substantial evidence indicates a role for the circadian system in regulating reward processing. Here we explore time of day effects on drug anticipation, locomotor activity, and voluntary methamphetamine (MA) and food intake in animals with ad libitum food access. We compared responses to drug versus a palatable treat during their normal sleep times in early day (zeitgeber time (ZT) 0400) or late day (ZT 1000). In the first study, usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 54 publications
2
14
0
Order By: Relevance
“…S4.2.2). Consistent with Keith et al (2013), the robustness of PAA was phasedependent; all mice fed peanut butter at ZT4 (6 of 6) exhibited PAA, but only 4 out of 7 mice displayed PAA when fed at ZT10. We next tested whether PAA persisted in constant conditions by removing the daily palatable meal.…”
Section: Wild-type Mice Anticipate Palatable Mealssupporting
confidence: 56%
See 3 more Smart Citations
“…S4.2.2). Consistent with Keith et al (2013), the robustness of PAA was phasedependent; all mice fed peanut butter at ZT4 (6 of 6) exhibited PAA, but only 4 out of 7 mice displayed PAA when fed at ZT10. We next tested whether PAA persisted in constant conditions by removing the daily palatable meal.…”
Section: Wild-type Mice Anticipate Palatable Mealssupporting
confidence: 56%
“…Several studies have shown that it is difficult to produce even weak anticipatory activity to scheduled palatable meals in mice (Hsu et al, 2010;van der Vinne et al, 2015). In contrast, Keith et al reported robust anticipatory activity to a daily offering of peanut butter in mice using a training protocol that combined scheduled chow and palatable meal training (Keith et al, 2013). In the current study we established a new simplified protocol (that does not require training) to establish PAA in mice during ad libitum chow access.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Rodents anticipate rewarding stimuli, including scheduled access to water, stimulants, and palatable meals 16 17 18 19 20 21 22 23 . In the current study, we sought to develop an approach to expose the free-running rhythm of the FEO by providing scheduled access to a high-fat/high-sugar palatable meal in the presence of ad libitum chow.…”
mentioning
confidence: 99%